Prevalence of sarcopenia in older women with pelvic floor dysfunction. (August 2021) - Silva, Rávida R.L.; Coutinho, Janaína F.V.; Vasconcelos, Camila T.M.; Vasconcelos Neto, José Ananias; Barbosa, Rachel Gabriel B.; B. Marques, Marília; Saboia, Dayana M.; C. Maia, Juliana
Abstract: Background: Sarcopenia is a determinant of age-related skeletal muscle weakness. In this sense, it is believed that there may be a pathophysiological association between pelvic floor dysfunction (PFD) and sarcopenia; however, few articles investigating an association between these two pathologies have been published. Objectives: To identify the prevalence of sarcopenia in older women with PFD and verify the association between the severity of PFD and the severity of sarcopenia. Methods: This cross-sectional study was undertaken in urogynaecology outpatient clinics in Fortaleza, Ceará, Brazil. Women with PFD aged ≥ 60 years were included. Women with cognitive impairments, amputations and/or limb fractures were excluded. Sociodemographic, anthropometric and PFD data were evaluated, and tests for measuring muscle strength, muscle mass and physical performance were performed. Results: In total, 217 women were included in this study; of these, 121 (55.8%) presented without sarcopenia, 71 (32.7%) presented with probable sarcopenia, 23 (10.6%) presented with confirmed sarcopenia, and two (0.9%) presented with severe sarcopenia. Regarding sarcopenia related to PFD, a higher prevalence of probable sarcopenia was observed in women with urinary incontinence (UI) ( n  = 55, 77.5%). Confirmed sarcopenia was more prevalent in women with pelvic organ prolapse (POP) ( n  = 19, 82.6%); among these cases, most women had POP of the anterior, posterior and apical compartments ( n  = 8, 42.1%). All the women with severe sarcopenia had UI and POP and, considering the specific types of these dysfunctions, the prevalence of severe sarcopenia was 50.0% in the women with UI and POP of the anterior and apical wall. The most severe stages of POP were associated with sarcopenia ( p  = 0.002). Conclusion: The prevalence of sarcopenia in women with PFD was high. Healthcare providers who assist women with PFD should consider the possibility of assessing sarcopenia, especially when faced with more extensive POP in older women. The evaluation of sarcopenia may play a role in the management of women with PFD.